Client Engagement with a Manualized Group Therapy Program. Issue 1 (2nd January 2017) - Brownlee, Naomi; Curran, David; Tsang, Sue Mun
ABSTRACT: A mixed-methods design was used to explore factors influencing client engagement, in a short-term, manualized, group therapy program for people with substance misuse problems. Associations between predictor variables and engagement with the group were explored. A number of pretreatment characteristics were found to be significantly related to client engagement. Thematic analysis of interviews with clients who dropped out of the group program revealed a number of other factors that influenced attrition among the sample. The results are worthy of consideration when assessing suitability of individuals for group treatment programs in addiction settings and more generally.